Effectiveness of debris flow mitigation strategies in mountainous regions. (December 2016) - Xiong, Muqi; Meng, Xingmin; Wang, Siyuan; Guo, Peng; Li, Yajun; Chen, Guan; Qing, Feng; Cui, Zhijie; Zhao, Yan
Debris flows represent major hazards in most mountainous regions of the world where they repeatedly result in disasters. In order to protect people and infrastructure against future debris flows, many debris flow catchments have been artificially intervened by employing various mitigation measures, including civil engineering works. However, the commonly adapted engineering measures, such as check dams, are not effective for every debris flow catchment, and the failure of such measures even causes more damage, e.g. the Sanyanyu debris flow catchment in Zhouqu, China, killed 1756 people. In order to research the effectiveness of engineering strategies and explore much more effective mitigation works for debris flows in the mountainous regions, we took the Bailong River catchment of Southern Gansu of China as study area, with special emphasis on Sanyanyu debris flow catchment (with civil engineering works) and Goulinping debris flow catchment (without civil engineering works), and comparatively analysed the two catchments. The comparative results show that both catchments have similar material source, geomorphological/environmental and climatic conditions, however, vegetation cover and rock hardness are poorer in Goulinping than in Sanyanyu, the catchment that underwent larger-scale debris flows, suggesting that the mitigation measures had been applied in Sanyanyu catchment were inappropriate. Subsequently, we simulated the effectiveness of controlling debris flow peak discharge with check dams at the lower part of Sanyanyu and Goulinping catchment using the Kanako simulator, and summarised argument based on the hypothesis and facts from positive and negative aspects. We draw the conclusion that it is not reasonable to build check dams in the two catchments and instead, drainage channels should be primarily considered for reducing debris flow hazards in such densely populated areas. Finally, we undertook detailed field investigations and experiments on the native plants in the region, and found that the ecological mitigation measure with planting Robinia Pseudoacacia on the debris flow deposits is an effective method to alleviate debris flow hazards. It is concluded that channel works combined with ecological measures are the preferable approaches to minimize the debris flow damage in debris flow catchments characterised with high mountains, concentrated rainfalls and active neotectonic movement.